Religious slaughter in European union : short review - Dobeic, Martin (Array, 2018)
The aim of this paper was to review current religious slaugtering processes and dillemas in EU. Stunning of animals before slaughter is a legally prescribed requirement in the EU intended to reach animal unconsciousness so that slaughter does not cause anxiety, pain, suffering or distress. In some European Union countries, religious slaughter is exceptionally allowed without stunning. Animals intended for religious slaughter must be healthy and undamaged. In order to meet these requirements, religious slaughtering in the EU is being implemented only in allowed and approved slaughterhouses. Slaughter can only be performed by authorized and educated operators. Regarding religious slaughter, there are many dilemmas in the EU about whether this methods of slaughter causes additional suffering of animals. Insofar as Muslim slaughter in some cases allows some methods of the preslaughter stunning, Jewish slaughter does not allow any stunning. Therefore, it is necessary to take into account the fact that in the future, it will be necessary to examine alternative stunning methods which will ensure the integrity of live animals before bleeding. At the same time, it is necessary to harmonize the guidelines for a harmonized procedures of handling animals before and after slaughtering and certifying of the meat originating from religious slaughter in order not to mislead consumers.